The suppression of geography in the exercise of otherness - Silva, Leonardo Luiz Silveira da (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
This article problematizes by means of five categorizations the negligence regarding the perception of the geographical differences between characteristics of individuals or States. This neglect is called suppression of geography in the exercise of otherness and is criticized through the phenomenological assumptions that explain the hybrid, permeable, and dynamic nature of cultures. The categorizations presented on in this article are cultural maps, arts, popular reactions, academic and literary texts, and geopolitical making. The article also presents the consequences of the suppression of geography in the exercise of otherness, indicating the importance of the theme in a contemporary historical moment marked by intense intercultural interlocution.
Keywords: Geografia; Cultura; Espaço; Alteridade.